Enhancement of Photocatalytic Activity of ZnO/SiO2 by Nanosized Pt for Photocatalytic Degradation of Phenol in Wastewater - R. M. Mohamed; M. A. Barakat (International Journal of Photoenergy)
ZnO-SiO2 nanoparticles were synthesized by a sol-gel technique from Zn(NO3)2⋅6H2O and tetraethyl orthosilicate (TEOS). The synthesized samples were further modified by nanosized Pt from H2PtCl6 solution through photoassisted deposition (PAD) and impregnation (Img) routes. The obtained samples were characterized by a series of techniques including X-ray diffraction (XRD), UV-Vis diffuse reflectance spectroscopy, N2 adsorption, extended X-ray absorption fine structure (EXAFS), and transmission electron microscopy (TEM). The photocatalytic activity of the Pt-ZnO/SiO2 was evaluated by photocatalytic degradation of phenol in synthetic wastewater under UV-irradiation. Results obtained revealed that the surface area and the photocatalytic activity of the prepared samples were increased in the order ZnO/SiO2 < PAD: Pt-ZnO/SiO2 < img: Pt-ZnO/SiO2. The surface area decreased from 480 to 460 and 450 m2/g, while the efficiency of the phenol degradation increased from 80 to 85 and 100%, with the ZnO/SiO2, Img: Pt-ZnO-SiO2, and PAD: Pt-ZnO-SiO2 samples, respectively.